Molecular mechanism of translational stalling by inhibitory codon combinations and poly(A) tracts. (20th December 2019) - Tesina, Petr; Lessen, Laura N; Buschauer, Robert; Cheng, Jingdong; Wu, Colin Chih‐Chien; Berninghausen, Otto; Buskirk, Allen R; Becker, Thomas; Beckmann, Roland; Green, Rachel
Abstract: Inhibitory codon pairs and poly(A) tracts within the translated mRNA cause ribosome stalling and reduce protein output. The molecular mechanisms that drive these stalling events, however, are still unknown. Here, we use a combination of in vitro biochemistry, ribosome profiling, and cryo‐EM to define molecular mechanisms that lead to these ribosome stalls. First, we use an in vitro reconstituted yeast translation system to demonstrate that inhibitory codon pairs slow elongation rates which are partially rescued by increased tRNA concentration or by an artificial tRNA not dependent on wobble base‐pairing. Ribosome profiling data extend these observations by revealing that paused ribosomes with empty A sites are enriched on these sequences. Cryo‐EM structures of stalled ribosomes provide a structural explanation for the observed effects by showing decoding‐incompatible conformations of mRNA in the A sites of all studied stall‐ and collision‐inducing sequences. Interestingly, in the case of poly(A) tracts, the inhibitory conformation of the mRNA in the A site involves a nucleotide stacking array. Together, these data demonstrate a novel mRNA‐induced mechanisms of translational stalling in eukaryotic ribosomes. Synopsis: A combination of in vitro biochemistry, ribosome profiling, and cryo‐EM defines molecular events that lead to ribosome stalling at inhibitory codon combinations and poly(A) tracts, demonstrating novel mRNA‐induced mechanisms slowing translational elongation by eukaryotic ribosomes. Inhibitory codon pairs and poly(A) tracts within mRNAs form decoding‐incompatible conformations in the decoding center of the ribosome. Direct effects of these structures on decoding are documented by high‐resolution ribosome profiling, kinetic studies and detailed cryo‐EM structural analysis. These data demonstrate a novel mRNA‐induced mechanism of translational stalling in eukaryotic ribosomes. The cryo‐EM structure of poly(A)‐stalled disomes reveals a novel conformation for collided ribosomes that rationalizes translational frameshifting. Abstract : A combination of in vitro biochemistry, ribosome profiling, and cryo‐EM reveals that elongation‐slowing mRNA elements stall ribosomes in decoding‐incompatible RNA conformations in the ribosomal decoding center.